Impact of population mobility on regional carbon emissions: empirical evidence from Australia - Guo, Hongbo (Frontiers in Environmental Science, 2024)
Exploring carbon emissions from the perspective of population mobility holds great theoretical and practical significance. It facilitates the accurate identification and understanding of factors influencing carbon emissions associated with population mobility, enabling the formulation of targeted carbon reduction policies to address Australia's sustainable economic development transition. Therefore, employing panel datasets covering international and domestic migration in Australia from 2007 to 2020, this paper conducts empirical analyses on the impact of population mobility on regional carbon emissions, aiming to devise more precise emission reduction strategies. The findings primarily reveal that domestic and international population mobility exert distinct impacts on carbon emissions. Specifically, domestic population mobility exhibits a negative correlation with carbon emissions, whereas international population mobility is positively associated with carbon emissions. Furthermore, significant heterogeneity in carbon emissions is observed between Australia's eastern and western regions, influenced by the regions' economic development and population size. In summary, this paper contributes to a more comprehensive understanding of CO2 emission changes through the lens of population mobility in response to global climate change.